(untitled) (Journal of the College of Basic Education, 2022)
The importance of the study came due to the emotional and mathematical intelligence having an important role for success in the educational life that pertains to sports academies and also by highlighting it as well as some basic skills in volleyball, which is a tool chosen by the researcher for the level of the skill scale, in addition to the above is to show the role of this psychological characteristic that She did not get her share of adequate studies in the sports field